Profitability of Cryptocurrency Trading Strategies Employed by Investors of a Philippine-Based Online Community: Basis for the Development of an Investor's Guidebook - Miriam Belle A. Abarquez; Ernielyn C. Esperanza; Jerwin A. Samson; Heidi C. Turiano; Genieve Aline A. Navela; Jesus P. Briones; Resty P. Umali; Joanna Paula E. Verano (International Journal of Marketing and Digital Creative, 2025)
The volatile and unpredictable nature of the cryptocurrency market poses significant challenges for making profitable trading decisions. This study investigated the profitability of cryptocurrency trading strategies employed by investors of a Philippine-based online community. A descriptive-correlational design was used, employing a Google Forms survey administered to 100 investors who are members of a private online cryptocurrency trading group based in a specific province in the Philippines. Data analysis included frequency, percentage, weighted mean, Pearson’s r, and t-test. Results indicated that most investors are young, educated professionals with employment in finance-related fields, suggesting a familiarity with trading systems. All trading strategies were perceived as generally effective in their contribution to profitability, with algorithmic trading and diversification showing the strongest positive correlations. Demographic variables—particularly sex, age, income, and profession—significantly influenced strategy choice. Younger, wealthier, and more professionally experienced individuals favored more advanced approaches, such as algorithmic trading and diversification. Based on the study's findings, the researchers proposed chapter guidelines for an investor’s guidebook, offering step-by-step strategies tailored to demographic characteristics to help optimize profitability and manage risk. Study limitations include the small and geographically limited samples, as well as the absence of longitudinal data. Future research should involve broader samples and the use of other research methods to validate these findings and explore the effectiveness of long-term cryptocurrency trading strategies.